Aggression Norms in the Classroom Social Network: Contexts of Aggressive Behavior and Social Preference in Middle Childhood. Issue 3 (28th September 2015) - Jackson, Daisy R.; Cappella, Elise; Neal, Jennifer Watling
Abstract: In a cross‐sectional sample of African‐American 2nd–4th grade students ( N = 681), we examine the moderating effects of classroom overt and relational aggression norms on peers' social acceptance of classmates who exhibit overt and relational aggression in urban schools. Extending theory and research on classroom norms, we integrate social network data to adjust aggression norms based on children's direct and indirect connections in the classroom. Results of multilevel models indicate that network‐based classroom aggression norms moderated relations between children's aggressive behavior and their social preference. Specifically, children benefited socially when their form of aggressive behavior fit with what was normative in the classroom social context. The moderating effect of classroom aggression norms was stronger for the association between overt aggression and social preference than relational aggression and social preference. Relationally aggressive youth were socially preferred by peers regardless of the classroom norm, although this positive association was magnified in classrooms with higher levels of relational aggression. Future research focused on aggression norms within classroom social networks are discussed and implications for school prevention efforts are considered.